Nanopore structure of PLA@SF aligned composite electrospun fiber membrane enhances growth behavior of peripheral nerve cells - Tao Feng; Yanfang Liu; Yehua Lv; Yang Shao; Lifeng Niu; Daguo Mi (Frontiers in Materials)
IntroductionOptimizing the physical microstructure of nerve grafts and enhancing their biological functions to create a microenvironment that favors the regeneration of damaged nerves can significantly improve the recovery of damaged nerve function. Fibers constructed using electrospinning technology can effectively replicate the 3D skeleton of the extracellular matrix (ECM). The impact of the porous characteristics of the fiber surface on cellular growth behavior has attracted considerable attention from researchers. However, there are few studies that have explored the synergistic influence of fiber surface nanotopology and silk fibroin (SF) on peripheral nerve cell growth patterns.MethodsThis study presents a polylactic acid (PLA)/silk fibroin (SF) composite fiber membrane featuring a nanopore structure on its surface. The following tests were used to characterize the performance of the fiber membrane: scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), tensile testing, water contact angle (WCA) measurements, degradation pH assessment, and topological structure stability tests. In addition, we also explored the biocompatibility, cytotoxicity, and the influence of the PLA@SF aligned porous composite fiber membrane on the growth behavior of peripheral nerve cells.ResultsResults from physical and chemical tests indicate that the PLA@SF composite fiber membrane exhibits an appropriate degradation rate, favorable mechanical and hydrophilic properties, and excellent topological structure stability. MTT assays demonstrate that the PLA@SF composite fiber membrane possesses good biological safety.DiscussionThe synergistic effect of the porous nanostructures and SF improved growth behavior of RSC96 cells: proliferation and migration.